KERJASAMA GURU BK DENGAN GURU MATA PELAJARAN DALAM MEMINIMALISIR MASALAH BELAJAR PESERTA DIDIK (STUDI DI SMA N 6 PADANG) - Putra, Jefri Sardika; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
The study backround because not maximal the coorperation which doing by Counselour and subject teacher and minimize activity of student problem, therefour researcher interested to studiying the form of coorperation between conselor. This study is background because there is existence the problems of education in school can finished by spesific personnel and some issues require cooperation to solve.This type of study is kuantitative descriptive with population of whol of the subject teacher and conselor in SMA N 6 Padang, amounting to 67 people, tools used like questionnaires and analysis data technique that percentage formula, the scale of valuation using scale formula of likert whereas intergrain using interval search formula. The result study showed that : 1) The coorperation of conselor with subject techer to minimize the problems of students learning in SMA N 6 Padang in enough good category. 2) The coorperation of conselor with subject teacher in guiding student to achieve self and feel in efective learning, with good category. 3) The coorperation of conselor with subject teacher in guiding student to know his self situation in optimizing the student perfomance with good category. 4) The cooperation of conselor in guiding student utilizing learning environment with good category.